Predicted Open Flow Rate Based on Capacity Test Well Data - Fu, Yu; He, Qinghui (International Journal of Natural Resources and Environmental Studies, 2024)
Open flow measurement in carbonate reservoirs directly affects the effectiveness of gas well production evaluation, assessment of reservoir potential, and guidance of safe production. In order to overcome the limitations of the traditional non-resistance flow calculation method, which relies on human adjustment and cannot meet the field demand in real time. In this study, based on the historical data and geological data of the blocks of the target gas reservoir, the production capacity test data of 8 wells and 13 wells were obtained. By using the K nearest neighbor method for data processing, a carbonate rock open flow prediction model based on the data from the capacity well test data was established, with a correlation coefficient of more than 0.92. The results of this study show that the predicted open flow rate is able to simplify the traditional complex mathematical calculation methods. This study provides support for capacity evaluation, assesses the potential of the gas reservoir, and helps the gas reservoir to develop appropriate safety production measures.